Parasite density and impaired biochemical/hematological status are associated with severe clinical aspects of canine visceral leishmaniasis. - Reis, Alexandre Barbosa (2012)
We have performed a detailed investigation in 40 dogs naturally infected withLeishmania infantum ( syn. chagasi), subdivided into three groups: asymptomatic (AD = 12), oligosymptomatic (OD = 12) and symptomatic (SD = 16), based on their clinical features. Twenty non-infected dogs (CD) were included as control group. Serological analysis, performed by IFAT and ELISA, demonstrated higher antibodies titers in SD in comparison to the AD. A positive correlation was found between parasite density in the spleen and skin smears as well as the bone marrow parasitism with clinical status of the infection. We observed that the progression of the disease from asymptomatic to symptomatic clinical form was accompanied by intense parasitism in the bone marrow. It is likely that this led to the impaired biochemical/hematological status observed. Finally, we believe that the follow-up of these parameters could be a relevant approach to be used as markers during therapeutic and vaccine evaluations.